2013
DOI: 10.1021/jp310619c
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Detection of Amyloid Marker Thioflavin T on Ag Nanoparticles by Surface-Enhanced Raman Scattering

Abstract: The vibrational characterization of the dye most commonly used for detection of amyloid aggregates Thioflavin T (ThT) was carried out by means of Raman and surface-enhanced Raman scattering (SERS) at different excitation wavelengths. The vibrational spectra obtained experimentally were subsequently analyzed using DFT calculations at the B3LYP/6-31+G** level. The Raman spectrum of ThT in aqueous solution correlates very well with the calculated spectrum of ThT with the torsional angle between the benzothiazole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Although signal loss can be seen for several signature peaks, the 1,601‐cm −1 peak showed the clearest gradual reduction with increasing peptide content (Figure b). Previous studies demonstrated that ThT SERS and fluorescence signals are very sensitive to the physicochemical properties of the surrounding medium . The underlying reason in the current case is suspected to be the hindrance exerted by the addition of intercalating beta‐rich peptide molecules around the dye, which can reduce the probability of several vibrational modes of the ThT molecule.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…Although signal loss can be seen for several signature peaks, the 1,601‐cm −1 peak showed the clearest gradual reduction with increasing peptide content (Figure b). Previous studies demonstrated that ThT SERS and fluorescence signals are very sensitive to the physicochemical properties of the surrounding medium . The underlying reason in the current case is suspected to be the hindrance exerted by the addition of intercalating beta‐rich peptide molecules around the dye, which can reduce the probability of several vibrational modes of the ThT molecule.…”
Section: Resultsmentioning
confidence: 77%
“…To demonstrate the use of MNS substrates for SERS‐based biosensing, ThT was chosen, as it is known to specifically intercalate within the beta sheets of Aβ(1–42)‐rich amyloid plaques . The molecule also demonstrates specific Raman peaks when covalently attached to plasmonic metal nanoparticles . The potential variation of ThT SERS intensities upon Aβ(1–42) interaction forms the basis of this biosensing platform, as similar complementary/specific interactions have been utilized to detect trace amounts of target biomolecules that causes alterations in the probe molecule‐originated SERS signal .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations